COVID-19 in pediatric nephrology centers in Turkey - Leventoglu, Emre; Ozdemir Atikel, Yesim; Nalcacioglu, Hulya; Dursun, Ismail; Dursun, Hasan; Yuruk Yildirim, Zeynep; Bakkaloglu, Sevcan A. (Tubitak Scientific & Technological Research Council Turkey, 2022)
Background/aim: There is limited data on COVID-19 disease in children with kidney disease. We aimed to investigate the characteristics and prognosis of COVID-19 in pediatric nephrology patients in Turkey. Materials and methods: This was a national, multicenter, retrospective cohort study based on an online survey evaluating the data between 11th March 2020 and 11th March 2021 as an initial step of a detailed pediatric nephrology COVID-19 registry. Results: Two hundred and three patients (89 girls and 114 boys) were diagnosed with COVID-19. One-third of these patients (36.9%) were between 10-15 years old. Half of the patients were on kidney replacement therapy: kidney transplant (KTx) recipients (n = 56, 27.5%), patients receiving chronic hemodialysis (n = 33, 16.3%) and those on peritoneal dialysis (PD) (n = 18, 8.9%). Fifty-four (26.6%) children were asymptomatic. Eighty-two (40.3%) patients were hospitalized and 23 (28%) needed intensive care unit admission. Fifty-five percent of the patients were not treated, while the remaining was given favipiravir (20.7%), steroid (16.3%), and hydroxychloroquine (11.3%). Acute kidney injury developed in 19.5% of hospitalized patients. Five (2.4%) had MIS-C. Eighty-three percent of the patients were discharged without any apparent sequelae, while 7 (3.4%) died. One hundred and eight health care staff were infected during the study period. Conclusion: COVID-19 was most commonly seen in patients who underwent KTx and received HD. The combined immunosuppressive therapy and frequent exposure to the hospital setting may increase these patients' susceptibility. Staff infections before vaccination era were alarming, various precautions should be taken for infection control, particularly optimal vaccination coverage.
Keywords: Children; COVID-19; kidney; pediatric nephrology; Turkey